Financial attributes, real earnings management and corporate tax planning of listed manufacturing firms in Nigeria - Maigoshi, Zaharaddeen Salisu; Tanko, Udisifan Michael (Journal of Accounting, Business and Finance Research, 2023)
The purpose of this study is to investigate the influence of financial attributes on the tax planning strategies of publicly listed manufacturing companies in Nigeria from 2012 to 2022. Additionally, it examines the moderating role of real earnings management (REM) in the relationship between financial attributes and tax planning. Data for this research were gathered from the annual reports of 41 publicly listed manufacturing firms in Nigeria. The study employed a correlational design using panel data analysis, with a fixed effects estimation applied to a simplified model and a moderated model. The results show that financial leverage positively and significantly affects the tax planning strategies of the listed manufacturing firms, and REM has a positive and significant influence on tax planning. Furthermore, REM was observed to significantly moderate the relationship between financial attributes and tax planning. Firms should engage in ethical and legal tax planning practices while taking their financial attributes into consideration. Companies need to be aware of the impact of REM on financial reporting and tax compliance and ensure that their tax planning aligns with relevant regulations.